Multicopy integration and expression of heterologous genes in the oleaginous yeast, Lipomyces starkeyi. Issue 3 (4th March 2015) - Oguro, Yoshifumi; Yamazaki, Harutake; Shida, Yosuke; Ogasawara, Wataru; Takagi, Masamichi; Takaku, Hiroaki
Abstract: The oleaginous yeast, Lipomyces starkeyi, is an excellent lipid producer with great industrial potential. However, methods for molecular breeding have not been established for L. starkeyi . We describe the development of a system for targeted rDNA integration of multiple copies of a gene into L. starkeyi genome by spheroplast–polyethylene glycol transformation.